The Effect of Employee Discipline And Work Results Against Performance Allowances for Civil Servants: PENGARUH TINGKAT KEDISIPLINAN DAN HASIL KERJA TERHADAP TUNJANGAN KINERJA - Kurnia, Tri Martha; Tobing, Josephine (Universitas Kristen Indonesia, 2017)
From the results of research on the level of discipline and Deliverables To Benefit Performance testing proves there is influence between the level of discipline and Results Working with Performance Benefits. Tests proved the first hypothesis that the level of discipline has influence significantly the performance to variable allowance. because thitung <t table with probability 0.0100> 0.005, then H1ditolak and H0 is accepted. Values of this coefficient indicates that the discipline has a positive and significant impact on the performance benefits. Results of testing the hypothesis has been proved.there is influence between the working results with the performance benefits. Tests proved the hypothesis that the results of the work affect the performance benefits because thitung 5,480> t table 2.012 with probability (sig) 0.000> 0.005 then H1ditolak and H0 is accepted. Values of this coefficient indicates that the results of the work has a positive and significant impact on the performance benefits.Keywords:d iscipline, Deliverables, Benefit Performance